IDENTIFIKASI KESULITAN MAHASISWA DALAM PENYUSUNAN SKRIPSI PRODI PGSD UNIVERSITAS MATARAM - Zain, Muhammad Irawan; Radiusman, Radiusman; Syazali, Muhammad; Hasnawati, Hasnawati; Amrullah, Lalu Wira Zain (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2021)
This qualitative research aims to identify the difficulties experienced by students in completing their paper assignments. This research was conducted on 144 students and alumni of PGSD University of Mataram. This research was conducted during the Covid-19 pandemic, so the research was conducted online. Data collection tools in this study were questionnaires and interviews. The research data analysis was conducted qualitatively. Based on the results of questionnaires and interviews conducted, several factors were identified that cause student to experience difficulties in completing paper, including individuals themselves, student agencies, families, and pandemic conditions. Based on the research results obtained, it takes several efforts that must be made by the institution in solving the problem of paper preparation, including strengthening cooperation between thesis supervisors, academic supervisors, validator lecturers, and completing and adding reference sources in institutional libraries.